IMPACT OF OWN-SOURCE, GENERAL, AND SPECIAL ALLOCATION FUNDS ON POVERTY IN EAST NUSA TENGGARA - Ninu, Angel Evangelist Foni Sopo (EP FEB UNS, 2024)
This study aims to analyze the impact of Regional Original Revenue, General Allocation Fund, and Special Allocation Fund on poverty in East Nusa Tenggara from 2018 to 2021. Using regression model analysis for panel data, the study examines 22 cities and districts in the region. The results indicate that these financial variables significantly influence poverty levels in East Nusa Tenggara. The findings underscore the importance of effective fiscal policy in poverty reduction strategies, suggesting that improvements in the management and allocation of these funds could have substantial implications for alleviating poverty in the region.